Behind, through and beyond capitalist platforms: Platformisation of work and labour in informational capitalism. (17th October 2022) - Zukerfeld, Mariano
Abstract : This article aims to put forward an overarching typology of platform-related work. First, it places the platformisation of productive processes within a characterisation of informational capitalism. Then it proceeds by distinguishing between work behind and through capitalist platforms. The former refers to the informational, industrial and service work and workers who keep the platforms up and running. The greater part of the article is devoted to discussing the latter. This second category is further divided into three sub-categories of work and workers: 'gig labour', 'prosumers' and 'self-employed owners'. Finally, platform work and labour beyond capitalist platforms are addressed, with a further sub-typology. Here, three types of beyond-capitalist platforms are identified: co-ops, commons-based peer production and state-owned agencies.